Individual actors and embeddedness in business-to-business interactions - Gonçalves, S. M.; Vinhas da Silva, R.; Teixeira, N. (Industrial Marketing Management, 2019)
Individual actors are hardly ever considered in business-to-business marketing literature. This paper uses Service-dominant Logic and Neo-institutional Theory as the bases for twelve case studies. These case studies provide a better understanding of how individuals who represent firms make sense of the social rules, norms, procedures, values, and beliefs of the network (i.e. institutional logics) where they are embedded and how the business interaction is shaped by those influences, through the individual behaviour. This paper makes two main contributions. First, we develop an empirical model of how individuals consider the institutional logics of the network in interactions with suppliers. Second, we present three patterns of individual behavior in interactions, different from what is often assumed by business-to-business researchers. Managerial contributions are also pointed out.